Nationwide survey of maternal screening for mother‐to‐child infections in Japan. (May 2014) - Yamada, Hideto; Tairaku, Shinya; Morioka, Ichiro; Ebina, Yasuhiko; Sonoyama, Ayako; Tanimura, Kenji; Deguchi, Masashi; Nagamata, Satoshi
Abstract Mother‐to‐child infections cause congenital infection with disease and sequelae. To evaluate a state of maternal blood screening for mother‐to‐child infections in Japan, we for the first time conducted a nationwide survey on obstetric facilities where regular maternity checkups were carried out. A questionnaire assessment involved an annual number of deliveries, scale of facilities and a state of maternal blood screening for eight pathogens. A high rate (73.7%) of reply to the questionnaire was achieved from 1990 facilities, covering 75.1% of annual number of delivery in 2011. The performance rates of blood screening were more than 99% for rubella virus, Treponema pallidum, human immunodeficiency virus (HIV), human T cell leukemia virus type 1 (HTLV‐1), hepatitis B virus, and hepatitis C virus, while the rate was found to be only 4.5% for cytomegalovirus (CMV), and 48.5% for Toxoplasma gondii with large differences in regions. Most of the facilities performed blood tests for rubella virus, Treponema pallidum, HIV, hepatitis B virus and hepatitis C virus once in early pregnancy, while approximately 28% of the facilities performed blood tests for HTLV‐1 once during the 2nd or 3rd trimester. Most of the facilities used HA tests for Toxoplasma gondii, whereas there was a wide variation in antibody measurement methods for CMV. Generally, the obstetric facilities in Japan have performed maternal blood screening properly according to the current recommendations. The results of this survey involve important information and are helpful for clinical practitioners.